Dangerous Terrain: Mapping the Female Body in Gonzales v. Carhart - Hill, B. Jessie (Columbia Journal of Gender and Law, 2010)
The body occupies an ambiguous position within the law. It is, in one sense, the quintessential object of state regulatory and police power. The body is the object that the state acts both upon and for; the body of the individual may, indeed, be subject to regulation and even physical intrusion in the name of the state’s power and duty to protect the health and safety of the “body politic.” At the same time, the body is often constructed in legal discourse as the site of personhood-our most intimate, sacred, and inviolate possession-implying that it is in some sense beyond the reach of the law. The inherent tension between these two concepts of the body permeates the law, but it is perhaps nowhere more prominent than in the constitutional doctrine pertaining to abortion. Abortion is one of the most heavily regulated medical procedures in the United States, and yet it is at the same time the subject of relatively robust constitutional privacy protections-often even treated as synonymous with the word “privacy” itself. This brief Article focuses on the rhetoric of the body in abortion law and more specifically on how the Supreme Court’s language constructs the female body in the recent case of Gonzales v. Carhart, which upheld the federal Partial Birth Abortion Ban Act (“PBABA”) against a constitutional challenge. A number of commentators have already remarked on the troubling rhetoric employed by Justice Kennedy’s majority opinion in that case, primarily because of its paternalistic and sentimental view of motherhood. But the focus of this Article is on the often overlooked, yet equally striking, language of the Court’s opinion that graphically describes and details the regulated abortion procedure itself.